Development of HOTS-based 2013 Curriculum Assessment Instruments in Elementary School - Marwan Pulungan; Toybah Toybah; Vina Amilia Suganda (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2021)
This study aims to develop a HOTS-based 2013 curriculum assessment instrument in the form of questions. The research subjects were fifth-grade students of the elementary school in Palembang. This research activity is development research using the ADDIE development model and the Tessmer evaluation method. The development stages include analysis, design, development, implementation, and evaluation. The prototype evaluation was carried out in stages: self-evaluation, expert reviews, one-to-one evaluation, small group evaluation, and field test evaluation. The results showed that the HOTS-based 2013 curriculum assessment instrument developed was declared valid, with a percentage of 89.5%. The trial results in the one to one and small group stages showed that the assessment instrument (HOTS questions) had a very good level of practicality, namely 84.3% for the one to one stage, and 83.2% for the small group stage. The effectiveness of the HOTS-based 2013 curriculum assessment instrument is at a low level, with an average score of 50. This means that the HOTS questions developed are still not effective in helping students think at higher levels, in this case, the ability to analyze, evaluate and create. This is as a note for researchers to review by carrying out further research.